Pemberdayaan Ekonomi Masyarakat Melalui Pembentukan Kelompok Sadar Wisata bagi Karang Taruna Kelurahan Bagan Deli Kecamatan Medan Belawan Kotamadya Medan - Siregar, Indra; Nasution, Benny B.; Sembiring, Rahmat W.; Rismawati, Rismawati (Politeknik Negeri Pontianak, 2023)
The purpose of forming a Tourism Awareness Group (Pokdarwis) for Karang Taruna members of the Bagan Deli Village is to increase the position and role of the community, especially the Karang Taruna Group as actors in tourism development and can synergize, partner with relevant stakeholders in improving the quality of tourism development in the Bagan Deli area Medan Belawan District, Medan Municipality. Bagan Deli is a kelurahan. The livelihoods of its citizens are mostly fishermen, laborers and some are unemployed. Based on the observations of the Community Service team and discussions with the Village Head and Chair of the Bagan Deli Youth Organization, it is planned that Community Service activities will be carried out by forming a Pokdarwis for youth organizations and creating a website as a promotion to introduce tourism potential and youth activities in the Bagan Deli area. The formation of Pokdarwis will provide skills and opportunities to earn income for Pokdarwis members and then the community. The availability of the website will be a forum for promoting tourism potential in the Bagan Deli area. So far, youth organizations in Bagan Deli have not provided much benefit, especially from an economic standpoint. The formation of the Pokdarwis will improve regional development and provide benefits for the welfare of the surrounding community.